Marriage Dispensation Policy In Children Protection: Evaluation Of Article 7 Paragraph (2) Of Law Number 16 Of 2019 Concerning Amendments to Law Number 1 Of 1974 Concerning Marriage) - Achmad Moelyono; Riza Yudha Patria; Fitri Setiyani Dwiarti (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
The age limit for marriage in Indonesia is regulated in Law Number 1 of 2019, stating that men and women are allowed to marry with a minimum age of 19 years. Then those who are less than 19 years old can apply for a marriage dispensation which is submitted to the Religious Court following the applicant's jurisdiction. Marriage dispensation in Indonesia has not yet responded to child protection, so it is still found that the age is below the age of the child whose application is granted. Departing from the arguments above, in this study will discuss the policy of marriage dispensation to protect children (Evaluation of Article 7 Paragraph (2) of Law No.-Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage)This research is a type of library research. This research is descriptive-analytical. The primary data in this study are the Qur'an, Hadith, the 1945 Constitution, Law Number 1 of 1974 concerning Marriage, Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, PP. Number 9 of 1975 as the implementing regulation of Law no. 1974, INPRES No.1/1991 on the Compilation of Islamic Law (KHI), Law No. 35/2014 on Child Protection, and a decision on marriage dispensation from the Lampung Provincial Religious Court. Using three theories of maslahah mursalah, the data analysis in this study uses deductive thinking techniques, then the author makes data analysis with qualitative analysis. Research results, regulations regarding the age limit for marriage as regulated in Law Number 16 of 2019, that the minimum age for marriage is 19 years for men and women. This has referred to the law on human rights and the law on child protection. About the granting of marriage dispensation in Indonesia, there is still no clarity written in the law. The marriage law in Indonesia adheres to the principle of maturity in marriage, meaning that everyone who carries out marriage must have maturity in terms of mental and psychological. It can be concluded that the policy regarding the age limit for marriage and dispensation for marriage in Indonesia correlates with Law no. 23 of 2002 concerning Child Protection, Law No. 39 of 1999 on Human Rights, and decisions from the world child protection agency UNICEF. In the review of mashlahah mursalah, This means that every person who carries out marriage must have maturity in terms of mental and psychological. It can be concluded that the policy regarding the age limit for marriage and dispensation for marriage in Indonesia correlates with Law no. 23 of 2002 concerning Child Protection, Law No. 39 of 1999 on Human Rights, and decisions from the world child protection agency UNICEF. In the review of mashlahah mursalah, This means that every person who carries out marriage must have maturity in terms of mental and psychological. It can be concluded that the policy regarding the age limit for marriage and dispensation for marriage in Indonesia correlates with Law no. 23 of 2002 concerning Child Protection, Law No. 39 of 1999 on Human Rights, and decisions from the world child protection agency UNICEF. In the review of mashlahah mursalah,If the granting of the dispensation is regulated at least 18 years of age, to mature the child in terms of education and maturity in terms of mental and psychological health, then this will lead to more benefit in it.